Aerobic Multicomponent Tandem Synthesis of 3‐Sulfenylimidazo[1, 2‐a]pyridines from Ketones, 2‐Aminopyridines, and Disulfides. Issue 27 (20th August 2013) - Ge, Wenlei; Zhu, Xun; Wei, Yunyang
Abstract: An aerobic CeCl3 · 7H2 O/NaI‐catalyzed C–H functionalization reaction was developed for the synthesis of 3‐sulfenylimidazo[1, 2‐ a ]pyridines from easily available ketones, 2‐aminopyridines, and disulfides without DMSO or peroxide as an oxidant. This three‐component tandem reaction process involves the formation of imidazo[1, 2‐ a ]pyridines followed by Friedel–Crafts sulfenylation in one pot under mild conditions. Both aryl and alkyl ketones afforded the desired products in good to excellent yields without the presence of other additives. Abstract : Aerobic oxidative three‐component tandem formation of C–N and C–S bonds in one‐pot! A CeCl3 · 7H2 O/NaI system is efficient for the synthesis of 3‐sulfenylimidazo[1, 2‐ a ]pyridines through a C–H functionalization strategy. Without the use of disulfides, a variety of imidazo[1, 2‐ a ]pyridines are obtained in good yields by using this protocol.